Influence of terbium (III) ions on the photocatalytic activity of TiO2 and CeO2 for the degradation of methylene blue in industrial effluents - de Campos, Mariana Bizari Machado [UNESP]; Cebim, Marco Aurélio [UNESP]; Meirelles, Mariana Rodrigues; Paris, Elaine Cristina; Rosa, André Henrique [UNESP] (Springer Nature, 2021)
This study reports the preparation of TiO2 and CeO2 doped with different quantities of terbium and discusses the influence of this dopant on the photocatalytic activity of the semiconductors, with respect to the degradation of methylene blue, under ultraviolet and solar radiations. The oxides obtained were characterized by X-ray diffraction, infrared vibrational spectroscopy, diffuse reflectance spectroscopy, scanning electron microscopy, and dispersive energy spectroscopy. The results indicate that the presence of the dopant in TiO2 favored the formation of the anatase crystalline phase to the detriment of rutile, increased the band gap energy, and decreased the size of the nanoparticles. Doping CeO2 with Tb resulted in a fluorite-type crystalline structure, reduced band gap, and smaller particle size. The photocatalytic activity decreases as the concentration of terbium increases regardless of the radiation source and nature of the oxide. Furthermore, a better performance was observed for all semiconductors excited by solar radiation in comparison to ultraviolet light. The samples of pure TiO2 and TiO2 doped with 0.5 and 1% terbium showed total removal of the dye after less than 120 min of reaction, while the samples of pure CeO2 and CeO2 doped with 0.5% terbium showed approximately 80% and 57% of dye removal after 120 min, suggesting that these materials can be promising for the treatment of industrial effluents.
Keywords: CeO2; Doping; Industrial effluent treatment; Photocatalytic activity; Solar radiation; Terbium; TiO2